2016
DOI: 10.1038/srep30622
|View full text |Cite
|
Sign up to set email alerts
|

Angiomotin like-1 is a novel component of the N-cadherin complex affecting endothelial/pericyte interaction in normal and tumor angiogenesis

Abstract: Transmission of mechanical force via cell junctions is an important component that molds cells into shapes consistent with proper organ function. Of particular interest are the cadherin transmembrane proteins, which play an essential role in connecting cell junctions to the intra-cellular cytoskeleton. Understanding how these biomechanical complexes orchestrate intrinsic and extrinsic forces is important for our understanding of the underlying mechanisms driving morphogenesis. We have previously identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…; Zheng et al . ) mRNA levels for N‐CAD were highest in the EC from female aorta. The relative expression hierarchy (strongest to weakest) was female aorta > male aorta > female SKM > male SKM (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…; Zheng et al . ) mRNA levels for N‐CAD were highest in the EC from female aorta. The relative expression hierarchy (strongest to weakest) was female aorta > male aorta > female SKM > male SKM (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…AMOTL1 belongs to the family of angiomotins (Amots) and is known as an adaptor protein, localizing in the nuclear, cytoplasmic, or membranous fraction in a cell context-dependent manner 24 . Growing evidence has certified that AMOTL1 controls biological activities, including migration, cell polarity, tight junction formation, and angiogenesis 11 , 25 , 26 . Furthermore, previous investigations have demonstrated that AMOTL1 exhibits cancerigenic activities in malignancies, such as breast cancer and cervical cancer 12 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This protein is also elevated in tumors. 51 53 Moreover, the potent tumorigenicity might be triggered through interactions between circ-AMOTL1 and c-myc; 49 and the alternative transcription form of the ENO1, MBP1, also interacts with c-myc P2 promoter, which explains the positive relationship between circ-AMOTL1 and ENO1 in another view. MiR-22-3p promotes cancer progression in cervical squamous carcinoma cells, 54 papillary thyroid cancer, 55 and pancreatic cancer; 56 meanwhile, it also acts as a tumor suppressor in colorectal cancer 57 and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%